Insulin resistance and diabetic macular oedema in type 2 diabetes mellitus. Issue 9 (11th June 2010) - Zapata, Miguel Angel; Badal, José; Fonollosa, Alex; Boixadera, Anna; García-Arumí, José
Abstract : Objective: To evaluate the association between insulin resistance and diabetic macular oedema in type 2 diabetes. Methods: Patients with type 2 diabetes who agreed to undergo blood sampling were enrolled into this cross-sectional study. Patients who had received treatment for macular oedema within the past 3 months and those with other retinal diseases were excluded. The following data were recorded: age, sex, time of diabetes evolution, HbA1c, ophthalmologic and systemic treatment, and lens status. Optical coherence tomography (OCT) was performed to determine the morphological patterns of macular oedema. Insulin resistance was established by a McAuley index of <6.3 and fasting insulin levels of >16 mU/l. Results: A total of 177 eyes from 90 patients were included; 27.1% of eyes were from insulin-resistant patients. There were no differences in age, time of evolution, sex, HbA1c level or lens status between insulin-resistant and non-resistant patients. Insulin-resistant patients were more likely to have exogenous insulin therapy (p<0.05; OR=3.8). An association was found between diabetic cystoid macular oedema and insulin resistance (Fisher exact test p=0.007; OR=2.53, 95% CI 1.52 to 4.2). There were no associations between insulin resistance and the other morphological patterns of oedema. Patients undergoing insulin therapy were found to have an association with a diffuse retinal thickening pattern on OCT (p=0.036; OR=1.4). However, no association was found between insulin therapy and the presence of cystoid macular oedema. Conclusions: The findings of this study indicate a relationship between insulin resistance and cystoid macular oedema that unrelated to the use of insulin. Insulin treatment was associated with diffuse macular oedema.